Glycyrrhetinic acid derivatives as Zika virus inhibitors: Synthesis and antiviral activity in vitro. (1st July 2021) - Baltina, Lidia A.; Lai, Hsueh-Chou; Liu, Ya-Chi; Huang, Su-Hua; Hour, Mann-Jen; Baltina, Lia A.; Nugumanov, Tagir R.; Borisevich, Sophia S.; Khalilov, Leonard M.; Petrova, Svetlana F.; Khursan, Sergey L.; Lin, Cheng-Wen
Graphical abstract: Highlights: Glycyrrhetinic acid (GA) derivatives (amides, semi- and thiosemicarbazones, and 1, 2, 3-thiadiazoles) were synthesized and tested as Zika virus inhibitors in vitro. Four active compounds were found among GA derivatives tested with IC50  < 1 μM against ZIKV replication. The lead compound was amide 13 containing 2-aminopyridine residue (IC50 0.13 μM, TI ˃ 384). Time-of-addition assays indicated the second lead compound 19 (1, 2, 3-thiadiazole 30-butyl GA) effectively inhibiting viral entry and post-entry stages. The molecular docking analysis demonstrated that lead compounds 13 and 19 forms a hydrogen-bond interaction with the catalytic triad (His51 - Asp75-Ser135) of ZIKV NS2B-NS3 protease. Abstract: Zika virus (ZIKV) is an arbovirus of the Flaviviridae family ( Flavivirus genus ), causing serious neurological complications, such as Guillain-Barre Syndrome (GBS) in adults and fetal microcephaly. Licensed vaccines or specific antiviral agents against ZIKV do not currently exist. Therefore, the search and development of anti-ZIKV agents are particularly relevant and necessary. Glycyrrhetinic (3 β -hydroxy-11-oxo-18 β H-Olean-12-en-30-oic acid) (GA) 1 is one of the well-known pentacyclic triterpenoids isolated from licorice root ( Glycyrrhiza glabra L., Gl. uralensis Fisher ) ( Leguminosae) possessing many biological features, including antiviral activity. This paper is devoted to the synthesis and studies of a number of nitrogen and sulfur-containing GA derivatives as ZIKV inhibitors. Sixteen GA and related triterpenoids (3 β -hydroxy-18 β H-Olean-12-en-30-oic acid and 3 β -hydroxy-11-oxo-18 β H-Olean-12(13), 18(19)-dien-30-oic acid) derivatives were synthesized (amides, semi- and thiosemicarbazones, and 1, 2, 3-thiadiazoles) and antiviral activity against ZIKV was studied in vitro, including the inhibitory assays on cytopathic effect (CPE), viral protein synthesis, and replication stages. Four active compounds were found among GA derivatives tested, 13 (3-O-acetyl-30-aminopyridine GA), 16 (3-semicarbazone-30-butyl GA), 18 (1, 2, 3-thiadiazole-30-methyl GA), and 19 (1, 2, 3-thiadiazole-30-butyl GA) with IC50  < 1 μM against ZIKV replication. These compounds had a stronger inhibitory activity on ZIKV-induced CPE and viral protein translation in infected cells as compared to derivatives of 11-desoxo-GA. The most active compound was amide 13 (IC50 0.13 μM, TI ˃ 384). Time-of-addition assays indicated that 1, 2, 3-thiadiazole ring is important for inhibiting viral entry stage (compounds 18 and 19 ), while the 30-butyl ester group influenced on post-entry stage (compound 19 ). The molecular docking analysis demonstrated that lead compounds 13 and 19 forms a hydrogen-bond interaction with the catalytic triad (His51 - Asp75-Ser135 ) of ZIKV NS2B-NS3 protease. Therefore, the active GA derivatives are promising for developing new antiviral agents against ZIKV infection.